Intergenerational Learning and Place-making in a Deindustrialized Locality: "Tracks of the Past" in Lanarkshire, Scotland. (2022) - Gibbs, Ewan; Henderson, Susan; Bianchi, Victoria
Abstract: This paper contributes to scholarship on the long experience of deindustrialization. It emphasizes contemporary place-making in navigating the much-changed socioeconomic landscapes that the closure of mills, mines, shipyards and factories have left behind. The 'half-life of deindustrialization' suggests these experiences have been received through understandings of labour and community with origins in the industrial era. 'Tracks of the Past' was a school-based education project themed around workers' occupation of Caterpillar's earth-moving machinery plant in Lanarkshire, Scotland. The occupation was a response to Caterpillar's shock closure announcement and the loss of 1, 200 jobs. It lasted 103 days between January and April 1987 when closure was reluctantly conceded. A Caterpillar Workers Legacy Group (CWLG) commemorated the occupation's thirtieth anniversary. During 2018, academics collaborated with the CWLG to develop a curriculum for a local high school class. 'Tracks' produced lessons where students engaged with archival sources and physical objects, interviewed members of the CWLG and conducted online research. The 'learning journey' montages that the students produced combined conversations in 2018 with sources from three decades earlier, often reflecting on the occupation as a historical episode in a highly localised context. Others implicated the closure within an international pattern, linking Caterpillar's divestment to the actions of multinationals in the contemporary global economy. In neither case did the invocation of the occupation lead to a straightforward translation of the occupation into contemporary workplace justice issues as the CWLG had hoped. However, these results did suggest a creative deployment of the past that rationalised the occupation with reference to contemporary deindustrialized contexts. These findings demonstrate the utility of the half-life through a lingering industrial past, but also demonstrate the need to conceptualise agents or custodians of labour history and challenge the linearity of passing time that an incrementally receding industrial era implicates.